Long Term Evaluation of Nanofibrous, Bioabsorbable Polycarbonate Urethane Grafts for Small Diameter Vessel Replacement in Rodents. (April 2020) - Eilenberg, Magdalena; Enayati, Marjan; Ehebruster, Daniel; Grasl, Christian; Walter, Ingrid; Messner, Barbara; Baudis, Stefan; Potzmann, Paul; Kaun, Christoph; Podesser, Bruno K.; Wojta, Johann; Bergmeister, Helga
Abstract : Objective: Biodegradable materials for in situ vascular tissue engineering could meet the increasing clinical demand for sufficient synthetic small diameter vascular substitutes in aortocoronary bypass and peripheral vascular surgery. The aim of this study was to design a new degradable thermoplastic polycarbonate urethane (dPCU) with improved biocompatibility and optimal biomechanical properties. Electrospun conduits made from dPCU were evaluated in short and long term follow up and compared with expanded polytetrafluoroethylene (ePTFE) controls. Methods: Both conduits were investigated prior to implantation to assess their biocompatibility and inflammatory potential via real time polymerase chain reaction using a macrophage culture. dPCU grafts ( n  = 28) and ePTFE controls ( n  = 28) were then implanted into the infrarenal abdominal aorta of Sprague–Dawley rats. After seven days, one, six, and 12 months, grafts were analysed by histology and immunohistochemistry (IHC) and assessed biomechanically. Results: Anti-inflammatory signalling was upregulated in dPCU conduits and increased significantly over time in vitro . dPCU and ePTFE grafts offered excellent long and short term patency rates (92.9% in both groups at 12 months) in the rat model without dilatation or aneurysm formation. In comparison to ePTFE, dPCU grafts showed transmural ingrowth of vascular specific cells resulting in a structured neovessel formation around the graft. The graft material was slowly reduced, while the compliance of the neovessel increased over time. Conclusion: The newly designed dPCU grafts have the potential to be safely applied for in situ vascular tissue engineering applications. The degradable substitutes showed good in vivo performance and revealed desirable characteristics such as biomechanical stability, non-thrombogenicity, and minimal inflammatory response after long term implantation.